Enhanced expression of farnesoid X receptor in human hepatocellular carcinoma. Issue 9 (1st February 2013) - Kumagai, Arisa; Fukushima, Junichi; Takikawa, Hajime; Fukuda, Toshio; Fukusato, Toshio
Abstract : Aim: The aim of this study was to investigate the expression of farnesoid X receptor (FXR) in human hepatocellular carcinoma (HCC) tissues and cell lines and evaluate its clinicopathological significance. Methods: Expression levels of FXR protein and mRNA in hepatocytes, hepatic stellate cells (SC), and HCC cells in human liver, HCC tissues and cultured cell lines were analyzed using immunohistochemical methods, western blotting (WB), and quantitative reverse transcription polymerase chain reaction (qRT–PCR). The relationship between FXR expression and clinicopathological parameters was also investigated. Results: Immunoreactivity for FXR was observed in nuclei of hepatocytes, SC and HCC cells. The intensity of nuclear FXR positive staining was comparable or increased in tumor cells of all HCC tissues when compared with hepatocytes of non‐tumorous liver tissues of the same patients as well as in comparison with metastatic colon cancers. A significant level of FXR expression in four of six human HCC cell lines was also confirmed, while it was undetectable in three cholangiocarcinoma cell lines. However, FXR protein and mRNA levels in HCC tissues determined by WB and qRT–PCR were lower than those in non‐tumorous liver tissues because of the high level of FXR expression in SC nuclei as detected by immunohistochemical double stain. Statistically significant relationships between FXR immunostaining intensity and high Ki‐67 labeling indices or a history of transcatheter arterial chemoembolization in HCC patients were also disclosed. Conclusion: Contrary to previous reports, preserved or enhanced expression levels of nuclear FXR were detected in HCC, indicating that FXR may play significant roles in the biological behavior of HCC.